A Károli Gáspár Református Egyetem megalapításának története - LÁNYI, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The History of the Foundation of Károli Gáspár Reformed University Plans to found a Hungarian Reformed university in Transylvania were conceived during the reigns of princes Gábor Bethlen (1622) and Ákos Barcsai (1658, then at the initiative of János Apáczai Csere), but unfortunately external circumstances prevented the establishment of such a university. At the end of the 18th century, the idea was raised again in Pest (József Vay, 1796). However, the circumstances made it only possible to establish a joint Evangelical-Reformed theological faculty (Pál Török, Theological Academy of Pest, 1855). In 1993, under the more favourable conditions of the regime change, the longed-for university could be founded, with the merger of the Theological Academy and the Teachers’ College of Nagykőrös and the establishment of a faculty of humanities in Budapest. Our study presents the circumstances, processes, debates, and key personalities behind the founding of the university 30 years ago.